Factors Affecting Performance-Based Budgeting as a Tool for Post-Covid-19 Management Control - Irmawati, Irmawati; Agustina, Maya; Ariyanda, Ariyanda (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research aimed to assess the impact of human resources, organizational commitment, and management control systems on performance-based budgeting at the Southwest Aceh Social Service, both simultaneously and partially. Research data was collected through a list of questions/questionnaires and documentation studies. The hypothesis was tested using multiple linear regression analysis, joint test, and partial test to determine jointly and partially the effect of the independent variable on the dependent variable at the 95% confidence level (α = 0.05). The object of this study was the human resources, organizational commitment, and management control systems influencing performance-based budgeting at the Southwest Aceh Regency Social Service. The sample size of this study was 38 employees.